Optimization of salinity range for rearing glass eel Anguilla bicolor bicolor - Ade Yulita Hesti Lukas; Daniel Djokosetiyanto; Tatag Budiardi; Agus Oman Sudrajat; Ridwan Affandi (Jurnal Akuakultur Indonesia)
ABSTRACT